Brain-Derived Neurotrophic Factor and Nerve Growth Factor Therapeutics for Brain Injury: The Current Translational Challenges in Preclinical and Clinical Research - Serena-Kaye Sims; Brynna Wilken-Resman; Crystal J. Smith; Ashley Mitchell; Lilly McGonegal; Catrina Sims-Robinson (Neural Plasticity)
Ischemic stroke and traumatic brain injury (TBI) are among the leading causes of death and disability worldwide with impairments ranging from mild to severe. Many therapies are aimed at improving functional and cognitive recovery by targeting neural repair but have encountered issues involving efficacy and drug delivery. As a result, therapeutic options for patients are sparse. Neurotrophic factors are one of the key mediators of neural plasticity and functional recovery. Neurotrophic factors such as brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) serve as potential therapeutic options to increase neural repair and recovery as they promote neuroprotection and regeneration. BDNF and NGF have demonstrated the ability to improve functional recovery in preclinical and to a lesser extent clinical studies. Direct and indirect methods to increase levels of neurotrophic factors in animal models have been successful in improving postinjury outcome measures. However, the translation of these studies into clinical trials has been limited. Preclinical experiments have largely failed to result in significant impacts in clinical research. This review will focus on the administration of these neurotrophic factors in preclinical and clinical stroke and TBI and the challenges in translating these therapies from the bench to the clinic.